2011 IEEE International Geoscience and Remote Sensing Symposium 2011
DOI: 10.1109/igarss.2011.6049710
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for high accuracy relative and absolute localization of TerraSAR-X / TanDEM-X data

Abstract: The German SAR (synthetic aperture radar) satellites TSX-1 and TDX-1 outperform former civilian space-borne radar sensors in terms of geometric accuracy. Recently, both satellites constitute the first bistatic SAR system in space: TanDEM -X. With the high geometric accuracy of both satellites, the geolocation of ground targets has to accurately consider signal propagation effects and geodynamic effects which formerly were negligible. The prediction of expected radar positions is additionally complicated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…The German SAR (Synthetic Aperture Radar) satellites Ter-raSAR-X (TSX-1) and TanDEM-X (TDX-1), launched in June 2007 and June 2010 respectively, provide an unprecedented geometric accuracy. Previous studies showed an absolute pixel localization accuracy for both sensors at the centimeter level [1][2][3][4][5]. However, we expect that by a thorough correction of all path delays and geodynamic effects even an improvement to the sub-centimeter level seems attainable [6].…”
Section: Introductionmentioning
confidence: 86%
“…The German SAR (Synthetic Aperture Radar) satellites Ter-raSAR-X (TSX-1) and TanDEM-X (TDX-1), launched in June 2007 and June 2010 respectively, provide an unprecedented geometric accuracy. Previous studies showed an absolute pixel localization accuracy for both sensors at the centimeter level [1][2][3][4][5]. However, we expect that by a thorough correction of all path delays and geodynamic effects even an improvement to the sub-centimeter level seems attainable [6].…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, almost all immediately neighboring measurement values typically differ by millimeters. Thus, on a short-term scale, our recent measurements point to a much better localization accuracy for TerraSAR-X than is known from our previous investigations [4] [6].…”
Section: Measurement Resultsmentioning
confidence: 75%
“…However, a thorough consideration of the varying amount of all geodynamic effects and signal propagation delays significantly decreases the spread of results in a localization measurement series [4]. In this respect, the standard deviation of the effect under consideration determines the relevance of the respective correction.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…최근에는 신호 지연 및 지각 오차 보정을 통해 서 TerraSAR-X가 cm 단위의 위치정확도를 확보 가능함을 Corner reflector를 통해 확인하였다 (Balss et al, 2013). Schubert et al, 2012;Balss et al, 2011;Balss et al, 2013). (Curlander et al, 1991;Frey et al, 2004).…”
unclassified